Development of Sharia Economic Law in Indonesia (Positivation of Zakat Law) - Suciyani Suciyani; Amrin Amrin (IHSA Institute, 2022)
In this study, we describe the development of sharia economic law in Indonesia with a focus on positivizing the Zakat Law. The method used in the literature review research is descriptive analysis approach with data collection techniques in the form of literature. The data analysis is using a normative qualitative method. Zakat regulation in Indonesia is still relatively new when compared to the time when Islam entered Indonesia itself. The history of zakat regulation in Indonesia can be classified into 3 (three) periods, namely (1) Pre-Independence, Zakat is only interpreted as an obligation that is managed individually. (2) During the Old Order and New Order, zakat management in the early days of independence was not much different from the period before independence. At this time, the management of zakat was still held by individuals, mosques, educational institutions that do not have the main activity in managing zakat. The government still chooses not to interfere with religious matters, including zakat. (3) During the Reformation Era, the Government began to accommodate zakat management with the issuance of a law, namely Law no. 38 of 1999 which was replaced by Law Number 23 of 2011